Understanding The Radicalism Movement In Indonesia: A Conflict Approach to the Rise of Terrorism - Nurus Shalihin (Institut Agama Islam Negeri (IAIN) Curup, 2017)
There is an ideology in every movement. Of course, that ideology that constructs the pattern of organizational movement. This phenomenon is an assumption in this paper, and will be broadly elaborated . In particularly; This study will describe the genealogy, reason, and patterns of salafism movement in Indonesia. The reason why this study seeks to understand the theme because the movement of salafism in Indonesia has emerged dramatically. It can be understood from the acts of terrorism that occurred. There are at least 4 acts of terrorism in 2000; 3 acts of terrorism in 2001; And 1 acts of terrorism in the 2000 Bali bombing which Is the most dramatic act of terrorism and the bombing action at J.W. Marriot hotel in 2003. These acts of terrorism are facts which suggest that the movement of salafism flourished in Indonesia. The data also encourages the study of why terrorism appears in Indonesia? What are the reasons? What is the root of the movement of salafism in Indonesia? The questions above are the research questions. And it all comes from the research paradigm chosen in this study, which is the paradigm of conflict. Assuming that acts of terrorism can be understood as a conflict process. It is not a single process that is the complete reason why terrorism arises, especially in Indonesia. The perspective of Marxism is considered quite possible to explain the factors causing terrorist acts, and the growing of the network in Indonesia. Actually, by using the paradigm of conflict; Violence, and horror acts perpetrated by terrorist networks can be detected why such malicious acts occurred in Indonesia. To analyze the data, this study uses the interpretative. And it's a concern to analyze the conflict between salafism, and others. This process allows the conclusion that the causal factor is the difference in doctrine between terrorism and the others-state, and the notion of neo-liberalism.